Teaching NeuroImage: Branching Dura Mater in Primary CNS ALK-Positive Anaplastic Large Cell Lymphoma - Wanakorn Rattanawong; Arnant Tekarnjnavanit; Chayoot Marukatat; Pasin Hemachudha; Thanakit Pongpitakmetha; Prakit Anukoolwittaya (Neurology, 2023)
A 22-year-old man presented with new-onset, gradually progressive diffuse headache for 2 months.He exhibited no apparent physical or neurologic abnormalities except for limited bilateral lateral rectus movement and bilateral papilledema on fundoscopic examination.An MRI examination of the brain showed multiple nodular-enhancing lesions along both sides of the falx cerebri with perilesional Figure 1 MRI Brain With Gadolinium Before Treatment T1-weighted imaging with gadolinium revealed multiple bilateral nodular-enhancing lesions along the falx cerebri, primarily located in the frontal lobe, and thickening of the dura mater (A: sagittal view, B: coronal view, and C: axial view).The red arrows demonstrated a branching network of thickened dura mater to adjacent enhancing nodular structures (A).Axial T2-fluid-attenuated inversion recovery image showed hypersignal intensity in the bilateral frontal lobes, suggesting the presence of perilesional edema (D).
Keywords: CNS Lymphoma Diagnosis and Treatment; Glioma Diagnosis and Treatment